Analysis and Properties of the Gutter Type Retard Systems - Staras, S.; Kleiza, A. (Elektronika ir Elektrotechnika, 1999)
Helical and meander gutter type structures are analysed. The structures are modelled by multiconducter lines with complicate cross-section. Numerical method is used for calculation of characteristic impedance of the multiconducter lines. As result it is shown that gutter type delay lines have better characteristics than simple lines.